Literasi Keuangan Pasar Modal untuk Optimalisasi Galeri Investasi Bursa Efek Indonesia STIE Ekuitas - Islami, Casni Fitria; Yuneline, Mirza Hedismarlina; Suryana, Usdi (Banking & Management Review, 2020)
This study aims to analyze the influence of student perceptions and the social-demographic variables on investment interest in the capital market as an effort to design a curriculum in Capital Market and Portfolio Management courses increase investment interest among students in the Capital Market. This study uses two analytical methods such as descriptive and quantitative analysis with a total sample of 100 students. In this study, the validity and reliability test using Alpha Cronbach, data transformation using the Successive Interval Method (MSI), and the normality test using the Kolmogorov Smirnov test. The results of this study indicate that the Financial Literacy Level of STIE Ekuitas students is Suff Literate and partially has positive effect on the interests of student stock investment. For social demographic variables, the study indicate that the financial Conditions is in sufficient level. The further results showed that even though parents' financial condition is good, it does not guarantee that students will actively invest because the variables studied are only limited to interests, not the investment decisions. Keywords: Financial Literacy, Social-Demographic, Investment Interest